Vivências de puérperas adolescentes sobre a escolha da posição do parto - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
The choosing of birth position must be a decision made by the woman consciously during the childbirth that way she is the leading figure during the whole process, consequently, preparation during pregnancy care is essential for the future parturient woman to obtain all the necessary information to her own beneficial during labor and concomitantly with the health professional who will assist the new mom and then provide a normal and humanized delivery. Therefore, the following study desire to present the reports of adolescent mothers about their experience regarding the choice of delivery position. This is a descriptive study with a qualitative approach concluded at the city of Macapá in the State of Amapá. During the study, nine puerperal teenagers participated, data collection took place from a semi-structured interview that was analyzed and categorized. Based on the results, three categories were defined was: I - The pregnant women's lack of knowledge about the childbirth positions, II - Knowledge X practice and III - The lithotomy position and its influence on perineal laceration. As a result, the fragility in the exchange of information during prenatal care was evident, and the require of guidance focused on labor and delivery is necessary.
Keywords: Parto Normal; Parto Humanizado; Mães Adolescentes; CNPQ::CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM OBSTETRICA; ODS 3 – Saúde e bem-estar; ODS 5 – Igualdade de gênero